Media Online sebagai Wadah Pemberdayaan Perempuan - Angelica Pramuditha Anggraini; Kiki Zakiah Darmawan (Jurnal Riset Jurnalistik dan Media Digital, 2022)
Abstract. In an era of increasingly sophisticated technology, media can change from print to online media, where online media has an effect on social life and environment. The discussion of online media can various, Perempuanberkisah.id makes the media a safe space for women survivors of violence, as a place for women's empowerment to eradicate gender injustice where women are more often the material of gender discrimination, both in the social environment and in the personal environment. The research method used in this study is a qualitative research method using virtual ethnographic analysis, with the symbolic interactional theory of George Herbert Mead and Herbert Blumer, the data collection techniques used are observation, documentation and in-depth interviews. The results show that based on (1) the mind at the media room level that Instagram is an online media that can be easily accessed, and media documents that show the meaning of empowerment and violence through user interaction. (2) Based on the concept of self (self) through the level of the media object, followers reflect themselves through the inspirational stories that exist in Women, (3) based on the environment (society) through the level of followers' experiences of empowerment and violence that have occurred in the virtual and real world so that followers provide safe space for survivors. Abstrak. Di era teknologi yang semakin canggih, media dapat berubah berawal melalui cetak menjadi media online, dimana media online tersebut berpengaruh pada kehidupan dan lingkungan bermasyarakat. Pembahasan media online dapat beraneka ragam, Perempuanberkisah.id menjadikan media sebagai ruang aman bagi para perempuan penyintas korban kekerasan, sebagai tempat pemberdayaan perempuan untuk menumpas ketidak-adilan gender dimana perempuan lebih sering menjadi bahan diskriminasi gender, baik di lingkungan sosial dan di lingkungan pribadi. Metode penelitian yang digunakan dalam penelitian ini adalah metode penelitian kualitatif dengan menggunakan analisis etnografi vitual, dengan teori interaksional simbolik George Herbert Mead dan Herbert Blumer, teknik pengumpulan data yang digunakan menggunakan observasi, dokumentasi dan wawancara mendalam. Hasil penelitian menunjukkan berdasarkan (1) pikiran (mind) pada level ruang media bahwa Instagram menjadi media online yang dapat diakses dengan mudah, dan dokumen media yang mempelihatkan bahwa pemaknaan tentang pemberdayaan dan kekerasan melalui interaksi pengguna. (2) Berdasarkan konsep diri (self) melalui level objek media pengikut merefleksikan dirinya melalui kisah inspiratif yang ada pada Perempuanberkisah (3) berdasarkan lingkungan (society) melalui level pengalaman pengikut tentang pemberdayaan dan kekerasan yang pernah terjadi di virtual maupun dunia nyata sehingga pengikut memberikan ruang aman bagi penyintas.